2008
DOI: 10.1016/j.schres.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional evaluation of adiponectin plasma levels in patients with schizophrenia and schizoaffective disorder

Abstract: Abstract:Background: In recent years, several studies showed increased rates of hyperglycaemia, diabetes, dyslipidemia, metabolic syndrome as well as cardiovascular disease in schizophrenic patients. The underlying mechanism, however, is poorly understood. Adiponectin is a recently identified adipocyte-derived protein, with low adiponectin levels being associated with metabolic abnormalities such as obesity, insulin resistance and type 2 diabetes. Methods: Fasting adiponectin levels were assessed in a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…Adiponectin induces direct inhibition of proinflammatory pathways, including those regulated by toll-like receptors (TLRs) (Neumeier et al, 2006), via inhibition of NF-κB in several cell types (Lira et al, 2012). Hipoadiponectinemia has been found in schizophrenic patients (Hanssens et al, 2008) and antipsychotic therapy also contributes to this condition (Birkenaes et al, 2009;Oriot et al, 2008;Wampers et al, 2012), suggesting that antipsychotic medication may influence adiponectin homeostasis.…”
Section: Antipsychotics Glucose Intolerance Insulin Resistance and mentioning
confidence: 99%
“…Adiponectin induces direct inhibition of proinflammatory pathways, including those regulated by toll-like receptors (TLRs) (Neumeier et al, 2006), via inhibition of NF-κB in several cell types (Lira et al, 2012). Hipoadiponectinemia has been found in schizophrenic patients (Hanssens et al, 2008) and antipsychotic therapy also contributes to this condition (Birkenaes et al, 2009;Oriot et al, 2008;Wampers et al, 2012), suggesting that antipsychotic medication may influence adiponectin homeostasis.…”
Section: Antipsychotics Glucose Intolerance Insulin Resistance and mentioning
confidence: 99%
“…Previous studies have reported that dysregulation of adipokines, i.e., adipocyte-derived peptides, is also linked with antipsychotic-induced metabolic abnormalities (Lu et al 2015;Sugai et al 2012). Leptin and adiponectin are key adipokines of interest owing to their critical roles in obesity and body fat distribution (Aye et al 2015;Baptista and Beaulieu 2002;Bredella et al 2011;Hanssens et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that obesity is significantly associated with the disruption of leptin signaling (Yang and Barouch 2007;Myers et al 2008). There have been reports on the associations between plasma adipokines and metabolic parameters including body mass index (BMI) in patients with antipsychotics (Baptista and Beaulieu 2002;Hanssens et al 2008;Henderson et al 2015;Jin et al 2008). It has been postulated that adiponectin levels might relate to mechanisms of weight gain and other metabolic dysregulations induced by antipsychotics (Bartoli et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Other studies found no statistically significant impacts of antipsychotics on glucose levels, glycohemoglobin, insulin levels or insulin resistance. 15 The incretin gastrointestinal hormones affect insulin secretion by pancreatic b cells. Glucose-dependent insulinotropic polypeptide (GIP) is one of two incretin hormones that stimulate an insulin response after an oral glucose challenge.…”
Section: Introductionmentioning
confidence: 99%